Resonance Rayleigh Scattering Spectra, Non-Linear Scattering Spectra of Congo Red-Copper(II)-Protein System and Its Analytical Application - Li†, Qiang; Song, Zhong-Rong; Yuan, Rui; He, Jia-Hong; Xu†, Qiang (Asian Journal of Chemistry, 2014)
A method to determine protein concentrations by using Congo red (CR)-Cu(II) complex as a spectral probe has been developed. In pH 6 Britton-Robinson buffer medium, the CR-Cu(II) complex could react with proteins such as bovine serum albumin, human serum albumin and ovalbumin to form the ternary ion-association complexes by virtue of electrostatic attraction and the hydrophobic force, which resulted in a great enhancement of resonance rayleigh scattering and resonance non-linear scattering such as second-order scattering and frequency doubling scattering. The maximum scattering peak was located at 278 nm for resonance rayleigh scattering, 542 nm for second-order scattering and 390 nm for frequency doubling scattering, respectively. The enhancements of the three scattering intensities (DI) were directly proportional to the concentration of proteins. The detection limits (3d) for the three proteins were 3.57-5.74 ng mL-1 for resonance rayleigh scattering method, 9.46-12.25 ng mL-1 for second-order scattering, 14.35-19.26 ng mL-1 for frequency doubling scattering method, respectively. Among them the resonance rayleigh scattering method exhibited the highest sensitivity and the bovine serum albumin system was more sensitive than other protein systems. The optimum condition such as the pH, the ion strength and the concentration of the probes for the reaction was investigated. In addition, the enhancement reasons of resonance rayleigh scattering, frequency doubling scattering and second-order scattering of the system are also studied. The present method has been applied to the determination of total proteins in human urine and serum samples with satisfactory results.